1998
DOI: 10.1177/009286159803200311
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Mouse Tumorigenicity Bioassay

Abstract: The International Conference on Harmonisation (ICH) has suggested the use of the newborn mouse bioassay as an alternative tumorigenicity assay. There are sufficient data to conclude that this animal model is highly sensitive to chemical carcinogens that exert their action through mechanisms involving the formation of covalently bound DNA adducts (exogenous d u c t s ) of the administered compound and the processing of these adducts to mutations.Mechanistic studies, including metabolism, DNA adduct formation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 65 publications
(83 reference statements)
2
21
0
Order By: Relevance
“…One study indicated that aflatoxin B1, which forms DNA adducts in both neonatal and adult tissues, induced tumors only in the neonate (Fu et al, 1998). This was presumed to be a result of the replication capacity and relative rate and efficiency of repair in the neonate versus the adult, thereby allowing for a higher probability of conversion of an adduct to a mutation.…”
Section: Mutagenic Efficiencymentioning
confidence: 99%
“…One study indicated that aflatoxin B1, which forms DNA adducts in both neonatal and adult tissues, induced tumors only in the neonate (Fu et al, 1998). This was presumed to be a result of the replication capacity and relative rate and efficiency of repair in the neonate versus the adult, thereby allowing for a higher probability of conversion of an adduct to a mutation.…”
Section: Mutagenic Efficiencymentioning
confidence: 99%
“…In the neonatal mouse bioassay, newborn mice are generally treated with carcinogens one to four times during the preweanling period (1-22 days of age) and killed at 8-12 months of age [6,7]. When tested with the proximate and ultimate carcinogenic metabolites of chemicals, such as the metabolites of benzo[a]pyrene, benzo[a]pyrene trans-7,8-dihydrodiol, and benzo[a]pyrene trans-7,8-diol-9,10-epoxide, the animals developed tumors much earlier and therefore were sacrificed at as early as 22-26 weeks of age [37].…”
Section: A Historical Background and General Considerationsmentioning
confidence: 99%
“…Genotoxic chemical carcinogens are defined as chemicals that exert tumorigenicity through mechanisms involving the formation of covalently bound carcinogen-DNA adducts that lead to mutation. In this review, nongenotoxic chemical carcinogens are defined as chemicals that exert tumorigenicity through secondary mechanisms that may include the formation of DNA adducts from endogenous lipid peroxidation or oxidative stress, induction of hypomethylation or hypermethylation, modulation of sex hormones, and induction of peroxisome proliferation [6,7].…”
Section: B Bioassay Of Genotoxic Chemical Carcinogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, over 150 chemicals have been evaluated in the neonatal mouse assay. In the US, the FDA has recently selected a variety of pharmaceuticals, which were either positive or negative in 2-year carcinogenicity bioassays and included genotoxic and non-genotoxic agents, for evaluation in the neonatal mouse assay (6,7).…”
Section: Introductionmentioning
confidence: 99%